2022
DOI: 10.1136/bmjopen-2022-063147
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication with ophthalmic drugs and its associated factors among ophthalmic patients attending three hospitals in Asmara, Eritrea: a cross-sectional study

Abstract: ObjectiveTo assess the prevalence and practice of self-medication and its associated factors among ophthalmic patients.DesignAn analytical cross-sectional study design was employed.SettingThree hospitals inAsmara, Eritrea.ParticipantsSamples of ophthalmic outpatients aged >18 years who visited the three hospitals in Asmara, Eritrea. Systematic random sampling was used to select the study participants.Data collection and analysisData were collected from September 2021 to October 2021 in a face-to-face interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…A significant proportion of respondents acknowledged engaging in the use of ophthalmic medication without obtaining a prescription, suggesting a notable prevalence of self-administration for the management of ocular symptoms. The present study's findings align with other research that has documented elevated levels of self-medication for ocular ailments [14][15][16]. The current study reveals a notable prevalence of self-medication with ocular drugs without a prescription, amounting to 97.6%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A significant proportion of respondents acknowledged engaging in the use of ophthalmic medication without obtaining a prescription, suggesting a notable prevalence of self-administration for the management of ocular symptoms. The present study's findings align with other research that has documented elevated levels of self-medication for ocular ailments [14][15][16]. The current study reveals a notable prevalence of self-medication with ocular drugs without a prescription, amounting to 97.6%.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study suggested that individuals may engage in self-treatment as a result of symptom recurrence or the belief that the disease does not necessitate professional care. Previous research has identified similar rationales when investigating the phenomenon of self-medication [12,14,23,24]. It is imperative to acknowledge and rectify these misconceptions while raising awareness about the potential hazards and constraints associated with self-medication in order to foster appropriate utilization of ophthalmic drugs.…”
Section: Discussionmentioning
confidence: 89%
“…The majority (58, 65.2%), had no complications. A study was done in the Netherlands, of 88 patients (41 men and 47 women), one had transient ocular hypertension, one had optic disc cupping without any glaucomatous defects in his visual field, and seven were given the diagnosis of cataracts [ 6 ]. More attention should be offered to the education of people about the serious health complication that can occur from this uncareful use.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate self-medication results in the irrational use of drugs, wastage of resources, and increased resistance to pathogens, which entails serious health hazards, such as adverse reactions and prolonged suffering [ 5 ]. This behavior includes buying medicines without a prescription, using leftover doses from previous prescriptions, sharing medicines with other family members or social groups, or misusing the medical prescription either by prolonging, interrupting, or modifying the dosage and the administration period [ 6 ]. When patients do not instill eye drops correctly, their clinical outcomes can be negatively affected [ 7 ].…”
Section: Introductionmentioning
confidence: 99%